Effect of Lawsonia inermis L. solution on Red Blood Cells of Pangasius hypophthalmus and were infected with Aeromonas hydrophila - Yunita Sari; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study was conducted on June to October 2017 in the Laboratory of Parasites and Fish Diseases, Fisheries and Marine Science Faculty, Riau University. The objective of this research was to understand the best of Lawsonia inermis L. solution for immersion in preventing the of Aeromonas hydrophila infection. There were five treatments applied namely negative control (Kn) was the fishes were not infected with Aeromonas hydrophila and were not immersed with Lawsonia inermis L. solution, positive control (Kp) was the fishes were not immersed Lawsonia inermis L. solution but were infected with Aeromonas hydrophila. The dose of Lawsonia inermis L. solution were 2000 ppm (P1), 3000 ppm (P2), 4000 ppm (P3). The fish was immersed for five minute in once a week for five times immersion. The result shown that the immersing with Lawsonia inermis L. solution in 2000 ppm (P1) was the best dose with a total value of erythrocyte 1.92x106 cell/mm3, 37.33% of hematocrit and 7.80 g/dL of hemoglobin and the survival rate (P1) was 93,33 % .Keywords: Lawsonia inermis L., Pangasius hypophthalmus, Aeromonas hydrophila, erythrocyte, hematocrit